Family emotional expression towards schizophrenic patients in Grhasia Mental Hospital Yogyakarta - Yuli Isnaeni; Hasna Mufida Nuraini (International Journal of Health Science and Technology, 2020)
This study aimed to identify the family emotional expressions towards patient with schizophrenia in Grhasia Mental Hospital Yogyakarta. The method of the study was Descriptive Study. The subjects were the family members of the patients with schizophrenia who visited the psychiatric clinic of Grhasia Mental Hospital Yogyakarta. The sample size was 45 respondents, which has been taken by the accidental sampling. The data were collected by questionnaire. The data were analyzed to determine frequency distribution of respondents’ characteristics and the levels of family emotional expressions. The results showed that most of the families (77,8%) who accompanied routine visited to the hospital were male, as parents or siblings respectively 33,3% and the fewest were couples (8,9%). Family age as many as 57,8% was in the range of 41-60 years and as many as 4,4% of those was aged 61 years and over. The majority of the family members or 34 respondents had high emotional expressions and only a small percentage or 11 respondents had low emotional expressions. Family members are expected to take a better care of schizophrenic patients by not frequently criticizing the patients and not showing too much emotional expression.